Strategi Pemberdayaan Lanjut Usia Sehat, Mandiri dan Produktif (Lansia Smart) - Rahmad Purwanto W; Endang Swastuti; Agus Wibowo (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2024)
The increasing number of elderly people is a development challenge that must receive the attention of all stakeholders, both local, national and global. Policies based on statutory regulations and government commitments are complete and require ongoing support. The aim of this community assistance and partnership is to improve the quality of health, productive economic, socio-cultural and socio-religious businesses within the institutional context of the church. The results of the mentoring show good achievements, increasing innovation in healthy living and group activities being active.